STRATEGI OPTIMALISASI TEMPAT PEMBUANGAN SAMPAH TERPADU (TPST) DI GILI TRAWANGAN - Selvia, Siska Ita; Danasari, Idiatul Fitri (JURNAL AGRIMANSION, 2023)
The Gili Trawangan Integrated Waste Management Site (TPST) is an asset belonging to the North Lombok Regency Regional Government, whose operationalization has had many obstacles. This research aims to formulate an appropriate strategy based on evaluating internal and external factors from various aspects, such as physical aspects, supporting infrastructure, institutions, financing, community participation, and laws/regulations. The approach used in this research is analytical and qualitative description. The analysis technique used is SWOT analysis, which consists of strengths, challenges, opportunities, and threats from waste management at Gili Trawangan TPST. The data consists of secondary data from related agencies such as the Environmental Service and the Gili Indah Village Office. In contrast, primary data was obtained from TPST documentation and interviews with key actors. The results of this research show that optimizing TPST performance can be achieved by implementing several strategies, such as: 1) Improving the planning system for a TPST location, infrastructure requirements, and institutional structure; 2) Develop policies regarding TPST management and levies in detail and based on supporting analysis such as (ability to pay analysis); 3) improve managerial capabilities, technical capabilities for TPST operationalization, monitoring and evaluation capabilities for each stakeholder involved; 4) Increase collaboration with academics, NGOs, investors, and others regarding technical guidance (TPST management, operationalization of various equipment at TPST, administration, funding, and waste recycling).